2009
DOI: 10.1097/01.hp.0000311549.85594.a3
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characterization of Capstone Depleted Uranium Aerosols I: Uranium Concentration in Aerosols as a Function of Time and Particle Size

Abstract: During the Capstone Depleted Uranium (DU) Aerosol Study, aerosols containing DU were produced inside unventilated armored vehicles (i.e., Abrams tanks and Bradley Fighting Vehicles) by perforation with large-caliber DU penetrators. These aerosols were collected and characterized, and the data were subsequently used to assess human health risks to personnel exposed to DU aerosols. The DU content of each aerosol sample was first quantified by radioanalytical methods, and selected samples, primarily those from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“… 17 The resulted metal particles may be rapidly oxidized in the air, then form oxide powder aerosols, which enter the human body by respiration, oral and wound contamination, even embedded in the human body. 18 , 19 , 20 , 21 After DU absorbed through respiration and digestive tract, they will enter the circulation, then mainly deposited in the alveoli and bones. Uranium in body is mainly excreted by the kidney, with excretion rate more than 90% within 24 h, and completely eliminated within 340 days.…”
Section: Killing Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“… 17 The resulted metal particles may be rapidly oxidized in the air, then form oxide powder aerosols, which enter the human body by respiration, oral and wound contamination, even embedded in the human body. 18 , 19 , 20 , 21 After DU absorbed through respiration and digestive tract, they will enter the circulation, then mainly deposited in the alveoli and bones. Uranium in body is mainly excreted by the kidney, with excretion rate more than 90% within 24 h, and completely eliminated within 340 days.…”
Section: Killing Factorsmentioning
confidence: 99%
“…Uranium in body is mainly excreted by the kidney, with excretion rate more than 90% within 24 h, and completely eliminated within 340 days. 18 …”
Section: Killing Factorsmentioning
confidence: 99%
“…An important parameter is the activity median aerodynamic diameter (AMAD) [ 35 ], which refers to the value of the particle size of 50% of the cumulative activity distribution. The deposition and retention of aerosols in the respiratory system is a difficult subject for experimental studies, which relates to the degree of dissolution [ 36 ] and absorption of these particles in body fluids after inhalation [ 37 , 38 ], as well as to particle size distribution [ 39 , 40 ] and aerodynamic properties [ 41 ]. Therefore, the fine particle fraction (FPF) of aerosols is defined, referring to the number/fraction of aerosols below the 0.1, 1, and 2.5 μm range [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the U.S. Army performed the Capstone Depleted Uranium (DU) Aerosol Study to provide information on the amount and characteristics of aerosol particles generated in or near vehicles hit by a large-caliber DU penetrator striking an Abrams or Bradley test vehicle [9][10][11][12]. Such studies reported measurements of mass particle concentration decay over time and mass particle distribution inside and outside tanks: total mass concentrations of thousands of mg m -3 were detected inside the tanks [8,11,12].…”
Section: Introductionmentioning
confidence: 99%